Nocardiosis and elevated beta-d-glucan in solid organ transplant recipients. (2021) - Ringer, Matthew; Radcliffe, Christopher; Kerantzas, Christopher A.; Malinis, Maricar; Azar, Marwan M.
Abstract: Beta-D -glucan (BDG) testing can expedite the diagnosis of invasive fungal infections in immunocompromised hosts. Elevated BDG levels have been reported in both in-vitro studies assessing cross-reactivity with Nocardia spp. and published cases of patients with nocardiosis, but there is little data on this association in solid organ transplantation (SOT) recipients. To explore this association, we conducted a case series of SOT recipients with culture-proven nocardiosis and BDG testing who received their care at our institution between 2016 and 2021. We found thirteen cases of nocardiosis in SOT recipients, of which three cases met our case definition of an elevated BDG. Their clinical courses are detailed in the present report. We found that BDG may be elevated in SOT with nocardiosis with no identified cause of false positive BDG, though a causal association cannot be determined. Future prospective studies that better evaluate the association between nocardiosis and BDG are warranted, as are studies that better characterize the possible variability in reactivity amongst Nocardia spp.